DESINDUSTRIALIZAÇÃO DO ABC: EMPREGO E DESEMPREGO EM TEMPOS DE MUDANÇA. - Ribeiro Júnior, Daniel (2008)
This paper is focused in the Brazilian ABC region (which comprehends Santo Andre, São Bernardo and São Caetano and four other cities in the São Paulo metropolitan area), emphasizing the industrial development and the eventual demographic density growth. The study is conducted by means of the analysis of the required manpower and its direct reflections in employment levels. In the first part the historical context is settled along with the analysis of the urbanization process that ended with the installation of the industrial plants in the area. The economical openings of the 90s, the application of new technologies and dministrative tools are also inserted in such context. At that point, the industrialization process is restructured in a way that the regional aptitudes are compromised: the so-called deindustrialization . The mainstream of the study is then concentrated in the automotive industry, by far the most relevant in the, and for the region. In the second part, a quantitative description of the behavior changes in the region and, at the same time, the unemployment in the industrial and service areas between the last decade of the 20th century and the beginning of the 21st one is done. A last, but not of lesser importance, the paper describes and explains the emerging of a new set of vocational aptitudes generated mainly by changes in the industrial profile. Analyzing issues like the shift in regional aptitudes and employment and unemployment based on available data from research institutes, correlations are made to determinate the present status of the employment level, the manpower status and the actual industrial process in the mentioned urban region.(AU)